Gastropoda di Perairan Budidaya Rumput Laut (Eucheuma sp) Kecamatan Suppa Kabupaten Pinrang - Djunaid, Rahmatullah; Setiawati, Henny (bionature, 2018)
Abstract. Indonesia has a high diversity of marine life, including gastropods. The distribution of gastropods varies in various locations at sea such as at the location of seaweed cultivation in Suppa Regency. These types of gastropods have not been identified even though the public knows the benefits of this organism. Therefore, efforts are needed to inventory these types of gastropods. The purpose of this study was to determine Gastropods living together in seaweed aquaculture locations (Eucheuma sp) in Suppa District. This research uses free roaming techniques along the seaweed cultivation location. The population is all types of gastropods that live together in seaweed farming locations. Samples are types of gastropods found at seaweed farming locations. Samples of abiotic and biotic factors along seaweed farming locations are also recorded as supporting inventory data. Gastropods were found there were 9 (nine) types that came from 8 (eight) genera, 5 (five) families. There are 3 species found in all sampling points, namely Cerithidea cingulata, Terebralia sulcata, and Terebralia palustris. Species found in certain locations and not found in other locations are Telecospium telecospium, Faunus ater, Rhinoclavis vertagus, Strombus microurceus, Nerita insculpta, and Monodonta labio. The suggestion of this research is to periodically observe the diversity of gastropod species in seaweed cultivation locations to determine patterns of interaction between organisms and the environment that occur seaweed cultivation locations.Keywords: gastropods, seaweed, pinrang district